Pengaruh Disiplin Kerja dan Komunikasi Terhadap Kinerja pada Dinas Koperasi dan Usaha Kecil Menengah (UKM) Kabupaten Lebak - Zakiyya Tunnufus (E-Journal Studia Manajemen, 2021)
Employee performance is an important foundation for the performance of an agency. Generally, in an organization or agency always want employees to have good performance or achievements. The level of success of an organization or agency depends on employee performance. One of the efforts to improve employee performance is by paying attention to work discipline and communication within the organization.This study aims: (1) To determine the effect of work discipline on the performance of the employees of the Cooperative and Small and Medium Enterprises Office of Lebak Regency. (2) To determine the effect of communication on the employee performance of the Cooperative and Small and Medium Enterprises Office of Lebak Regency. (3) To determine the effect of work discipline and communication on the performance of the employees of Dinas Koperasi Dan UKM Kabupaten Lebak. The research method used is using quantitative methods. The population in this study were 35 people. The research sample used saturated samples. The analysis technique in this study uses multiple regression analysis techniques, analysis of the correlation coefficient, the coefficient of determination, the T test and the F test with the SPSS version 20 program. The results showed partially work discipline had a positive and significant effect on employee performance. Partially communication has a positive and significant effect on employee performance. Meanwhile work discipline and communication together have a positive and significant effect on employee performance with a contribution of 78.6% to employee performance and the remaining 21.4% is contributed by other variables not examined. In this study, to improve employee performance in order to pay attention to work discipline, especially the dimensions of attendance and communication, especially the dimensions of internal communication.